Response of LibertyLink and WideStrike Cotton to Varying Rates of Glufosinate. (December 2015) - Dodds, Darrin M.; Main, Christopher L.; Barber, L. Thomas; Burmester, Charles; Collins, Guy D.; Edmisten, Keith; Stephenson, Daniel O.; Whitaker, Jared R.; Boykin, Deborah L.
Abstract : Field studies were conducted in Alabama, Arkansas, Georgia, Louisiana, Mississippi, North Carolina, and Tennessee during 2010 and 2011 to determine the effect of glufosinate application rate on LibertyLink and WideStrike cotton. Glufosinate was applied in a single application (three-leaf cotton) or sequential application (three-leaf followed by eight-leaf cotton) at 0.6, 1.2, 1.8, and 2.4 kg ai ha −1 . Glufosinate application rate did not affect visual injury or growth parameters measured in LibertyLink cotton. No differences in LibertyLink cotton yield were observed because of glufosinate application rate; however, LibertyLink cotton treated with glufosinate yielded slightly more cotton than the nontreated check. Visual estimates of injury to WideStrike cotton increased with each increase in glufosinate application rate. However, the injury was transient, and by 28 d after the eight-leaf application, no differences in injury were observed. WideStrike cotton growth was adversely affected during the growing season following glufosinate application at rates of 1.2 kg ha −1 and greater; however, cotton height and total nodes were unaffected by glufosinate application rate at the end of the season. WideStrike cotton maturity was delayed, and yields were reduced following glufosinate application at rates of 1.2 kg ha −1 and above. Fiber quality of LibertyLink and WideStrike cotton was unaffected by glufosinate application rate. These data indicate that glufosinate may be applied to WideStrike cotton at rates of 0.6 kg ha −1 without inhibiting cotton growth, development, or yield. Given the lack of injury or yield reduction following glufosinate application to LibertyLink cotton, these cultivars possess robust resistance to glufosinate. Growers are urged to be cautious when increasing glufosinate application rates to increase control of glyphosate-resistant Palmer amaranth in WideStrike cotton. However, glufosinate application rates may be increased to maximum labeled rates when making applications to LibertyLink cotton without fear of reducing cotton growth, development, or yield.